0104 Effect of Dinner Timing on Nocturnal Metabolism in Healthy Volunteers. (12th April 2019) - Gu, Chenjuan; Brereton, Nga; Schweitzer, Amy; Cotter, Matthew; Borsheim, Elisabet; Wolfe, Robert R; Jun, Jonathan C
Abstract: Introduction: Consuming calories later in the day is associated with obesity and metabolic syndrome. We hypothesized that eating a late dinner alters metabolic function during sleep in a manner that promotes obesity. Methods: We compared metabolic effects of routine dinnertime (RD, 18:00) versus late dinnertime (LD, 22:00) with a fixed sleep period (23:00-07:00) on the daily metabolic profile of healthy volunteers in a randomized crossover study. An isocaloric diet was administered at 8:00, 13:00, 18:00, or 22:00. For RD, dinner (35% daily kcal) was given at 18:00 and a snack (10% kcal) was given at 22:00; for LD, these meals were reversed. Peripheral venous blood samples were collected at 1-hour intervals from 17:00 to 12:00 the next day on both visits. We assessed plasma triglycerides (TG), free fatty acids (FFAs), glucose, insulin, cortisol, and sleep architecture. Participants ingested a lipid tracer, [ 2 H31 ]palmitate with dinner to measure fatty acid oxidation. Time series data was analyzed using mixed effects regression models. Results: To date, eight participants (5 male and 3 females) aged 26.4 ± 0.7 years old, with a BMI of 24.1 ± 1.2 kg/m 2 completed the study. During sleep, LD increased plasma glucose (β=16.8 mg/dl, P <0.001), insulin (β=15.4 μU/ml, P <0.001), cortisol (β=1.5 μg/dl, P =0.017), and decreased plasma FFA (β=-0.1 mmol/l, P <0.001). Morning glucose, insulin, cortisol and FFA levels were not significantly different between two visits. Morning TG were increased by RD (β=17.4 mg/dl, P <0.001). The evening postprandial period following LD was characterized by higher glucose and lower FFA as compared to RD ( P <0.05). Fatty acid oxidation will be measured by serial enrichment of plasma 2 H2 0 (pending). Dinner time did not affect sleep architecture. Conclusion: LD increases nocturnal glucose, insulin, cortisol, and decreases FFA. The inhibition of nocturnal lipolysis with LD may lower morning TG. Overall, LD leads to an anabolic state during sleep that might promote the development of obesity. Support (If Any): R01HL135483, R03HL138068